Development of digital pop-up book media to enhance fifth-grade students’ concentration in electrical energy learning - Mochammad Raden; Arina Restian (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
Education in Indonesia is currently transforming through the implementation of the Independent Curriculum (Kurikulum Merdeka), which emphasizes meaningful learning and a student-centered approach. However, initial observations at Muhammadiyah 08 Dau Elementary School revealed low levels of concentration and understanding among fifth-grade students regarding electrical energy, due to the abstract nature of the content and the limitations of interactive learning media. This study aimed to develop a Digital Pop-up Book as an innovative medium to improve students’ concentration and understanding, using the ADDIE development model involving 20 students. Data were collected through observations of student engagement, concentration questionnaires, and conceptual understanding tests before and after the use of the media. Validation results showed very high feasibility (86% from content experts and 82% from media experts), while classroom implementation showed an increase in concentration from the medium to the high category, as well as significant improvements in learning outcomes. This study demonstrated that the Digital Pop-up Book is efficacious in improving focus, participation, and understanding of electrical energy concepts, while providing theoretical contributions to the development of visual-interactive learning media for abstract science materials and supporting the implementation of the Independent Curriculum in elementary schools.